CONSTRUCTIVE FEEDBACK IN TEACHING AND LEARNING: A PERSPECTIVE FROM BIOLOGY TEACHING PRACTICE - Nguyễn Thị Ái Minh (Tạp chí Khoa học Đại học Đà Lạt)
This article highlights the benefits of providing constructive feedback for both teachers and students, especially for student teachers. A theoretical framework on constructive feedback, which formed the basis of the research, was synthesized from literature. This was followed by a study on the practice of providing constructive feedback in teaching and learning within a module of Biology Teaching Practice at Dalat University.